Shift in detrital sedimentation in the eastern Bay of Bengal during the late Quaternary - Babu, C. Prakash; Pattan, J.N.; Dutta, K.; Basavaiah, N.; Prasad, G. V. Ravi; Ray, D. K.; Govil, P. (My University, 2010)
Down-core variations of granulometric, geochemical and mineral magnetism of a 70-cm long sediment core retrieved from the eastern Bay of Bengal abyssal region were studied to understand sedimentation pattern and sediment provenance during the last ∼12 kyr BP. Based on down-core physical and elemental variations, three units were identified: unit 3 (70–43 cm) is a ∼30 cm thick clayey silt organic carbon-rich (0.5–0.92%) turbidite probably delivered by the Brahmaputra River during the late Quaternary period. Units 2 (43–24 cm) and 1 (24–0 cm) represent enhanced and reduced supply of coarse-grained detrital sediments from the Ganges River during early and late Holocene period, respectively. Increased terrigenous supply dilutes calcium carbonate (CaCO3) and biogenic elements (P, Ba and Cu) in units 3 and 2. On the contrary, a reduction in detrital input enhances CaCO3 and biogenic elements in unit 1. Lithogenic elements (Ti, Al, K and Rb) and shale-normalized REE patterns in all three units suggest terrigenous source. The shift in provenance from the Brahmaputra to the Ganges derived sediments is evident by a sharp increase in sediment grain size, increased concentration and grain size assemblages of magnetic minerals, lithogenic elements concentration and Lan/Ybn ratio. This study highlights terrigenous dilution on biogenic sedimentation in the eastern Bay of Bengal sediments.
Keywords: Bay of Bengal; Sediment core; Calcium carbonate; Dilution; Detrital; Biogenic; Turbidite; Ganges-Brahmaputra